2021
DOI: 10.1186/s13058-021-01392-0
|View full text |Cite|
|
Sign up to set email alerts
|

Molecular analyses of triple-negative breast cancer in the young and elderly

Abstract: Background Breast cancer in young adults has been implicated with a worse outcome. Analyses of genomic traits associated with age have been heterogenous, likely because of an incomplete accounting for underlying molecular subtypes. We aimed to resolve whether triple-negative breast cancer (TNBC) in younger versus older patients represent similar or different molecular diseases in the context of genetic and transcriptional subtypes and immune cell infiltration. Pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
40
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 54 publications
(118 reference statements)
4
40
1
2
Order By: Relevance
“…Recent studies showed that younger patients with TNBC more often have high sTILs tumors when compared with older patients and that there is an inverse correlation between sTILs levels and the number of positive lymph nodes. 12,23 Moreover, the sTILs distribution in our study was in line with the sTILs distribution in the young patient subgroup of the study reported by Aine et al 23 One explanation might be the changing composition and function of immune cells with age. 24 Further research is needed to increase our understanding of the interaction between the immune system, the hormonal system, age, and breast cancer.…”
Section: Discussionsupporting
confidence: 91%
“…Recent studies showed that younger patients with TNBC more often have high sTILs tumors when compared with older patients and that there is an inverse correlation between sTILs levels and the number of positive lymph nodes. 12,23 Moreover, the sTILs distribution in our study was in line with the sTILs distribution in the young patient subgroup of the study reported by Aine et al 23 One explanation might be the changing composition and function of immune cells with age. 24 Further research is needed to increase our understanding of the interaction between the immune system, the hormonal system, age, and breast cancer.…”
Section: Discussionsupporting
confidence: 91%
“…Further sub-analysis of ER receptor status of our cohort showed a significant correlation between the ER negative status with young age ( p =0.0001), larger tumor size ( p <0.0001), high grade tumor ( p <0.0001), and high Ki67 expression ( p <0.0001). A similar observation of high Ki67 expression by immunohistochemistry and mRNA expression in young patients by Aine et al 33 from Lund University, Sweden.…”
Section: Discussionsupporting
confidence: 79%
“…TNBC is commonly seen in women 50 years of age and younger and the other breast cancer subtypes tend to occur more often in women aged 60 or older. One study reported [3] that there was no correlation between age and invasive disease-free survival (DFS) or overall survival (OS) after adjuvant chemotherapy. However, a different study [4] reported that shorter survival times, distant DFS, and breast cancer-specific survival were found in the older age group with TNBC.…”
Section: Introductionmentioning
confidence: 99%